Budaya Hook-Up Pada Online Dating Tinder - Madarina, Farahiah Almas (Asketik: Jurnal Agama dan Perubahan Sosial, 2020)
This paper discusses hook-up as a culture in online dating applications. Tinder, as the most popular dating app in Indonesia, facilitates its users to find partners online. With just one swipe on the phone screen, a person can select a partner in seconds; very practical, easy and fast. This phenomenon has led to the spread of hook-ups as a dating practice that encourages casual sexual encounters without any emotional connection. To review this phenomenon, the writer uses Ritzer's McDonaldization concept applying the principles of fast food restaurants to describe the global homogenization of hook-up culture which also has reached Indonesia. These principles include efficiency, calculating power, predictive power and control applied in modern society.